TEACHER’S DIFFICULTIES IN ONLINE LEARNING MATHEMATICS LESSONS IN TEGALYOSO STATE ELEMENTARY SCHOOL - Ria Lestari (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2021)
AbstractThis study aims to determine the difficulties of teachers in online learning of mathematics subjects at SD Negeri Tegalyoso for the 2020/2021 academic year. This research is a qualitative research with data collection techniques, namely observation, interviews and documentation. Sampling of data was done by purposive sampling. The subjects of this research are principals and teachers. The data analysis stage was carried out, namely data reduction, data presentation, and verification. The results of this study indicate that the analysis of teacher difficulties in online learning of mathematics subjects is as follows: (1) The difficulties of teachers in teaching mathematics online are difficult to instill learning concepts, difficult to carry out learning, difficult to coordinate with parents, difficult to know student understanding, teachers teach more long, difficult to make learning videos. (2) The factors that cause teacher difficulties are that students do not have cellphones, students' internet quota is limited, parents' attitudes are indifferent, parents' education is low, they have to wait for students' parents to finish working to collect student assignments, learning that occurs only in one direction. (3) The impact of the teacher's difficulties is that the material is not delivered optimally, the teaching time becomes longer, the level of student understanding is less measurable, and student learning achievement is not satisfactory. (4) The solutions to overcome these difficulties are increasing study time, extending the time for collecting assignments, allowing students to go to school, home visits, and multiplying learning videos.